2019
DOI: 10.33206/mjss.459684
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Kamu Yönetimi Öğrencilerinin Suriyeli Sığınmacılara İlişkin Tutumları

Abstract: Bu çalışmada, 2017-2018 eğitim-öğretim yılında Dokuz Eylül Üniversitesi İktisadi ve İdari Bilimler Fakültesi Kamu Yönetimi Bölümü'nde eğitim gören öğrencilerin Suriyeli sığınmacılara ilişkin tutumlarını ve tutumları ile ilişkili değişkenleri belirlemek amaçlanmıştır. Kesitsel tipteki bu çalışmada "Mültecilere Ait Tutum Ölçeği" kullanılmıştır. Ölçekte toplam skor olumsuz tutum üzerinden hesaplanmıştır. Puan yükseldikçe tutum da olumsuzlaşmaktadır. Çalışmaya toplam 467 Kamu Yönetimi öğrencisi katılmıştır (Ulaşma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Different results can be seen in the literature regarding the attitudes of women and men towards Syrians. While some studies state that women are more positive in attitudes towards Syrians (Ankaralı et al, 2017; Topal et al, 2017), some studies did not find a significant difference (Çimen & Quadir, 2018; Kaya, 2019; Şen & Şimşek, 2019). In the present study, it is thought that one of the reasons for the lack of difference between men and women is due to the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Different results can be seen in the literature regarding the attitudes of women and men towards Syrians. While some studies state that women are more positive in attitudes towards Syrians (Ankaralı et al, 2017; Topal et al, 2017), some studies did not find a significant difference (Çimen & Quadir, 2018; Kaya, 2019; Şen & Şimşek, 2019). In the present study, it is thought that one of the reasons for the lack of difference between men and women is due to the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth exploring the relevance of intergroup contact theory (Allport, 1954), and seeing if increased contact with Syrians reduces the negative attitudes of the youth toward Syrians. Several studies on university students' attitudes in Turkiye (Afyonoğlu & Buz, 2021;Ozaydin, Tanyer, & Akin, 2021;Şen & Keskin, 2019) support the argument that contact with refugees reduces anti-refugee sentiments, but further research is warranted. Future research should include different dimensions of socialization such as the quality and frequency of the contact.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also revealed that positive family attitudes toward Syrians, positive peer attitudes toward Syrians, and having a Syrian acquaintance increase students' scores on the "attitudes toward Syrians" scale, where higher scores indicated lower prejudice. The study by Şen and Keskin (2019) on university students also demonstrated that the students who had Syrian friends and whose families had positive attitudes toward Syrians increased positive student attitudes. Another study (Ankaralı, Pasin, Karacan, Tokar, Künüroğlu, Çaça, Özislam, & Şahingöz, 2017) on university students also demonstrated that family's attitudes toward Syrians affected students' attitudes.…”
Section: Young People's Attitudes Toward Syrians In Turkiyementioning
confidence: 93%
See 1 more Smart Citation
“…Verilerin normal dağılabilmesi için normallik testi sonuçlarının p>0,05 veya Skewness ve Kurtosis değerlerinin -1,5 ile +1,5 arasında olması gerekmektedir (Tabachnick ve Fidell, 2007). Çizelge 2'de görüleceği üzere verilerin dağılımı her iki (Aldemir, 2019;Şen ve Keskin, 2019;Aslan vd., 2018;Kabaklı-Çimen ve Ersoy-Quadir, 2018;Ankaralı vd., 2017;Kara vd., 2016;Topkaya ve Akdağ, 2016). Temas Kuramı (Pettigrew, 1998a;1998b) ile farklılık gösterdiği dikkat çekmektedir.…”
Section: Verilerin Değerlendirilmesiunclassified